A scoping review: Investigating the extent and legal process of cauda equina syndrome claims for UK physiotherapists. (December 2021) - Leech, Rachel L.; Selfe, James; Ball, Suzanne; Greenhalgh, Susan; Hogan, Gareth; Holway, Janene; Willis, Emma; Yeowell, Gillian
Abstract: Introduction: Cauda Equina Syndrome (CES) is a condition where early identification and treatment is crucial to avoid potentially life changing devastating effects. This paper reviews the extent and process of CES litigation amongst UK physiotherapists. Methods: A well-established framework by Arksey and O'Malley was followed when completing the current scoping review. Records were identified via a comprehensive search of three databases as well as website and grey literature searching. Data was extracted and a descriptive analysis and thematic summary were formed. Results and discussion: A total of N = 1639 records were identified, following removal of duplicates and screening of titles and abstracts N = 211 full text records were screened and N = 39 were included for full analysis. Conclusions: This study is the first to investigate the extent and process of CES litigation for physiotherapists in the UK. Our data suggest that between 2009 and 2021 there were 15 CES claims recorded against physiotherapists which is 0.7% of all CES claims recorded in the UK. In terms of the legal process for CES claims, there is currently limited information for physiotherapists and what steps they would need to take once they receive notification they are being sued. Registration: The current paper is registered with OSF registries (DOI 10.17605/OSF.IO/6FCXN). Highlights: Cauda Equina Syndrome litigation in physiotherapy. Extent of Cauda Equina Syndrome litigation amongst UK physiotherapists. Legal process for litigation amongst UK physiotherapists. Review of legal process for UK physiotherapists. Review of extent of Cauda Equina Syndrome litigation for UK physiotherapists.